PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) TERHADAP HASIL BELAJAR SISWA PADA MATERI SPLTV DI SMA NEGERI 2 MANADO - Letunggamu, Maria Priskila; Pitoy, Cori; Pulukadang, Rosiah J (LPPM Politeknik Saint Paul Sorong, 2024)
This research investigates the application of the cooperative learning model, specifically the Team Assisted Individualization (TAI) approach, in enhancing the learning outcomes of high school students in the topic of System of Linear Equations in Three Variables (SPLTV) at SMA Negeri 2 Manado. The study is motivated by the challenges students face in mathematics, particularly in contextual problems and mathematical modeling, leading to outcomes that do not meet the Minimum Completeness Criteria (KKM). The research employs a quasi-experimental design, contrasting one class utilizing the TAI model with another using conventional teaching methods. Data were collected via pre-tests and post-tests, which revealed a significant difference in average scores favoring the TAI model. Results indicate that TAI not only improves knowledge but also engages students actively, promoting collaboration and reducing the perception of mathematics as a difficult subject. The study suggests the integration of cooperative learning strategies to enhance student motivation and understanding in mathematics education, contributing to the development of effective teaching methodologies.